0319 Transparent Paper as a Medium of Copying and Design in the Early Modern Architectural Workshop - Anna Bortolozzi (RIHA Journal)
This article explores the use and function of the lucido technique in architectural workshops from the Renaissance through the late eighteenth century. By examining evidence from written sources and key drawing collections, the study compares the copying practices of architects with those of artists. The findings reveal that transparent paper was not appreciated as a copying medium in Europe’s architectural workshops until the mid-eighteenth century. When employed, transparent paper was primarily used for copying figure and ornamental drawings that were challenging to transfer using the pricking technique. The paper argues that the marginalization of transparent paper in architectural practice was possibly due to the coating process and the characteristics of the substances employed – vegetable oils and resins – which were incompatible with the working environment of architects. It was only with the commercialization of machine-made wove transparent paper in the early nineteenth century that architects and engineers began to systematically adopt this medium.